Factors influencing the adoption of appropriate electronic waste recycling practices in Sub-Saharan Africa: Empirical literature review - Benjamin MWALUGENI; Jacob KIHILA; Alphonce KYESSI (Smart Cities and Regional Development Journal)
The main focus of this paper is to provide a thorough examination of the factors influencing the adoption of appropriate e-waste recycling practices in Sub-Saharan Africa. Objective: Specifically, this study assessed global e-waste recycling and policy issues and the factors influencing the adoption of appropriate e-waste recycling practices in sub-Saharan Africa. Prior work: This paper is built upon available literature that has been published in the area of e-waste recycling. The paper utilized publications from different developed and developing countries by examining legal and institutional frameworks, infrastructures, recycling practices, etc. Approach: This study used a desk review approach to conduct a systematic literature review of research articles collected from various databases. Implications: The findings of this study provide insights into the factors influencing the adoption of appropriate e-waste recycling practices by policy makers and all e-waste stakeholders. This provides a path for the implementation of sustainable development goals that aim to protect human health and the environment. Value: This study revealed that the absence of policies, regulations and recycling infrastructure are some of the factors affecting the adoption of e-waste recycling in sub-Saharan Africa. However, some countries within the region, such as South Africa, Rwanda and Uganda, have enacted regulatory frameworks for e-waste management, which have enabled them to facilitate the adoption of e-waste recycling practices in their countries. Other factors include economic incentives and market opportunities, which play critical roles in driving the adoption of appropriate e-waste recycling practices. Moreover, factors such as public awareness, education, and technology are fundamental in the region.